2017
DOI: 10.1037/com0000077
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transposition tasks in Indian sloth bears (Melursus ursinus) and Bornean sun bears (Helarctos malayanus euryspilus).

Abstract: Spatial transposition tasks assess individuals' ability to represent nonvisible spatial object displacements. Several nonhuman mammal species have been tested on this task including primates, cats, and dogs, but to date, great apes seem the only taxon that has repeatedly and consistently solved spatial transposition tasks. The authors investigated the ability of captive sloth and sun bears to solve spatial transposition tasks. Both species belong to the same taxonomic group as cats and dogs, but unlike them an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…In children, the ability to solve the transposition task emerges later than the ability to solve invisible displacement tasks ( Sophian and Sage, 1983 ; Sophian, 1984 ; Barth and Call, 2006 ), suggesting that this is a more challenging type of problem. A large number of mammals either fail to solve transposition tasks or may use associative strategies to guide their choices, including cats ( Doré et al, 1996 ), dogs ( Doré et al, 1996 ; Rooijakkers et al, 2009 ; Fiset and Plourde, 2013 ), wolves ( Fiset and Plourde, 2013 ), wild boars ( Albiach-Serrano et al, 2012 ), pigs ( Albiach-Serrano et al, 2012 ), goats ( Nawroth et al, 2015 ), dolphins ( Jaakkola et al, 2010 ), and bears ( Hartmann et al, 2017 ). Despite this selection of species including herbivores, omnivores, and carnivores, as well both domesticated and wild animals, only parrots ( Pepperberg et al, 1997 ; Auersperg et al, 2014 ) and primates ( Beran and Minahan, 2000 ; Call, 2001 , 2003 ; Beran et al, 2005 ; Barth and Call, 2006 ; Rooijakkers et al, 2009 ) have been conclusively shown to succeed at object transposition tasks.…”
Section: Differences In Intelligence Across Speciesmentioning
confidence: 99%
“…In children, the ability to solve the transposition task emerges later than the ability to solve invisible displacement tasks ( Sophian and Sage, 1983 ; Sophian, 1984 ; Barth and Call, 2006 ), suggesting that this is a more challenging type of problem. A large number of mammals either fail to solve transposition tasks or may use associative strategies to guide their choices, including cats ( Doré et al, 1996 ), dogs ( Doré et al, 1996 ; Rooijakkers et al, 2009 ; Fiset and Plourde, 2013 ), wolves ( Fiset and Plourde, 2013 ), wild boars ( Albiach-Serrano et al, 2012 ), pigs ( Albiach-Serrano et al, 2012 ), goats ( Nawroth et al, 2015 ), dolphins ( Jaakkola et al, 2010 ), and bears ( Hartmann et al, 2017 ). Despite this selection of species including herbivores, omnivores, and carnivores, as well both domesticated and wild animals, only parrots ( Pepperberg et al, 1997 ; Auersperg et al, 2014 ) and primates ( Beran and Minahan, 2000 ; Call, 2001 , 2003 ; Beran et al, 2005 ; Barth and Call, 2006 ; Rooijakkers et al, 2009 ) have been conclusively shown to succeed at object transposition tasks.…”
Section: Differences In Intelligence Across Speciesmentioning
confidence: 99%
“…Since publication of the broad reviews of tool use referred to above, several recent studies conducted under experimental conditions have confirmed the presence of special and cognitive abilities in captive giant pandas (Ailuropoda melanoleuca), American black bears (Ursus americanus), Bornean sun bears (Helarctos malayanus uryspilus), and Indian sloth bears (Melursus ursinus) (Perdue et al, 2009;Vonk and Beran, 2012;Zamisch and Vonk, 2012;Perdue, 2016;Amici et al, 2017Amici et al, , 2019Hartmann et al, 2017). Of particular relevance to this study are the experimental demonstration of tool use by captive brown bears (Ursus arctos) (Waroff et al, 2017) and a similar experiment with captive Indian sloth bears (Amici et al, 2019) in which the subjects were unsuccessful at demonstrating similar abilities.…”
Section: Introductionmentioning
confidence: 96%
“…In humans, the ability is known to be present at a relatively early developmental stage [ 4 ]. Many non-human species have tested positively for at least some levels of object permanence (see review in [ 5 ]; for example, chimpanzees ( Pan troglodytes ): [ 6 – 9 ], bonobos ( Pan paniscus ): [ 6 , 7 ], orangutans ( Pongo pygmaeus ): [ 6 , 8 ], gorillas ( Gorilla gorilla ): [ 6 , 10 ], Eurasian jays ( Garrulus glandarius ): [ 11 ], bears ( Melursus ursinus and Helarctos malayanus euryspilus ): [ 12 ], dogs ( Canis lupus familiaris ):[ 13 ] and cats ( Felis catus ): [ 14 ]). Subjects belonging to these diverse species searched in the correct place when food or another object was seen to disappear (visible displacement).…”
Section: Introductionmentioning
confidence: 99%